A review of the stabilization of tropical lowland peats - Zulkifley, M.T.M.; Ng, T.F.; Raj, J.K.; Hashim, R.; Bakar, A.F.A.; Paramanthan, S.; Ashraf, M.A. (2013)
The Deep Mixing Method, which involves the formation of in situ stabilized peat columns, is suitable for deep peat stabilization, whereas the mass stabilization technique is used to stabilize the soil of shallow peat deposits instead of the costly and problematic removal and replacement method. The concept of soil-cement stabilization involves the addition of water to cement, resulting in a chemical process known as cement hydration. Stabilization of peat by cement, which requires a significant strength increase in the cement-stabilized peat or organic soil, is attributed largely to physicochemical reactions that include cement hydration, hardening of the resulting cement paste and interactions between soil substances and primary and secondary cementation hydration products. The factors that affect these physicochemical reactions and the interactions of peat soil-cementation products that influence peat stabilization are the amount of solid particles, the water: soil ratio, the quantity of binder, the presence of humic and/or fulvic acids, the soil pH and the amount of organic matter in the peat. With the Air Curing Technique, stabilized peat samples for unconfined compressive strength (UCS) tests were kept at a normal air temperature of 30 ± 2 °C and strengthened by gradual moisture content reduction instead of the usual water-curing technique or water submersion methods that have been common practice in past experiments involving the stabilization of peat with cement. The principle of using the Air Curing Technique to strengthen stabilized peat is that peat soil at its natural moisture content contains sufficient water (water content from 198 to 417 ) that, when mixed with cement, a curing process takes place that causes the stabilized peat soil to gradually lose its moisture content and to become drier and harder throughout the curing period. This process does not require the addition of water.